DECOMPOSITION OF TENSOR PRODUCT OF COMPLETE GRAPHS INTO CYCLES AND STARS WITH FOUR EDGES - Ezhilarasi, A. P; Ilayaraja, M; Muthusamy, A (TWMS journal of applied and engineering mathematics, 2023)
In this paper, we prove that the necessary conditions are sufficient for the existence of a decomposition of tensor product of complete graphs into cycles and stars with four edges. Keywords: Graph decomposition, Cycle, Star, Product graph. AMS Subject Classification: 05C51, 05C70